A Strategic Model to Improve Faculty Publication Performance in Buddhist Higher Education Institutions in Indonesia. - Ardianto, Hendri; Waskito, Budhi; Haninun, Haninun (Islamic University of Kalimantan MAB Banjarmasin, 2026)
This study aims to develop and empirically test a strategic model for enhancing faculty publication performance at Buddhist Higher Education Institutions in Indonesia, which continue to face challenges related to the productivity and quality of scientific publications. Specifically, the study examines the effects of research culture, compensation, and mindful leadership on faculty publication performance, both directly and indirectly through research motivation as a mediating variable. A quantitative explanatory research design was employed, involving 157 faculty members from 12 Buddhist Higher Education Institutions in Indonesia. Data were collected using a Likert-scale questionnaire and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 3.0 software. The findings reveal that research culture, compensation, and mindful leadership have positive and significant effects on research motivation and faculty publication performance. Furthermore, research motivation is confirmed to mediate the relationships between the three independent variables and faculty publication performance. This study concludes that strengthening research culture, implementing a fair compensation system, and adopting mindful leadership practices are key strategic approaches to enhancing research motivation and faculty publication performance in Buddhist Higher Education Institutions in Indonesia. Keywords: Research culture; mindful leadership; compensation; research motivation; faculty publication performance; Buddhist higher education institutions in Indonesia.